Comparison of conventional and shell vial cultures for detecting cytomegalovirus infection. - Rabella, N (1990)
We tested 606 specimens for cytomegalovirus infection. Fifty-two specimens were positive by conventional culture versus forty-three by pre-cytopathic effect detection. Twenty-nine specimens were positive by both methods. Because of toxicity, specimens should be set up on both conventional and shell vial culture systems to achieve maximum sensitivity.